Treatment of coral reef aorta with open surgical endarterectomy - case report of a unique clinical entity - Novotný, R; Sutoris, K; Kostrouch, D; Růžička, P; Čermáková, H; Froněk-, J; Janoušek, L (Rozhledy v chirurgii, 2025)
INTRODUCTION: Coral reef aorta (CRA) is a rare clinical entity characterised by hard, protruding calcifications in the juxta and supra-renal aorta, which cause haemodynamically significant stenosis of the aorta and its branches. We are presenting a case report of a 65-year-old female patient with bilateral 30-meter claudication on both lower extremities and a haemodynamically significant stenosis of the left renal artery. CASE REPORT: The patient underwent computed tomography angiography (CTAG) of the abdominal aorta and lower extremities. CTAG revealed severe abdominal aortic wall calcification with circular atherosclerotic calcification in the area of the renal arteries branch off, causing haemodynamically significant stenosis of the aorta and the left renal artery. The patient was scheduled for an elective open surgery. The left retroperitoneal approach dissects the abdominal aorta, including both renal arteries. -Cross-clamps were placed on both renal arteries, the subrenal aorta and the suprarenal aorta, just below the superior mesenteric artery. Circular aortic calcifications protruded through the aortotomy, and aortal endarterectomy was performed. The calcific plaques extend-ing to the left renal artery were dissected similarly. Identically, an endarterectomy of both common iliac arteries orifice was performed. RESULT: The patient was discharged on the 8th postoperative day with excellent renal parameters, normal left kidney perfusion, and without limiting claudications on both lower extremities. Currently, we have a 12-month follow-up with the patient. CONCLUSION: CRA is a rare clinical entity. The optimal treatment has yet to be established. Up-to-date, the gold standard treatment for CRA is surgical endarterectomy.
Keywords: endarterektomie; Renal Artery Obstruction; atherosclerosis; Computed Tomography Angiography; Endarterectomy; Atherosclerosis; vaskulární kalcifikace; lidé; senioři; CT angiografie; Aortic Diseases; Aged; obstrukce renální arterie; nemoci aorty; endarterectomy; Aorta, Abdominal; Vascular Calcification; ženské pohlaví; aorta abdominalis; Aorta; renal artery; Humans; Female